1993
DOI: 10.1159/000187311
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcome in Patients with Glomerulonephritis and Antineutrophil Cytoplasmic Autoantibodies

Abstract: We investigated the clinical features and outcome of 60 patients with antineutrophil cytoplasmic autoantibodies with cytoplamic staining (C-ANCA)- and with (peri)nuclear staining (P-ANCA)-associated glomerulonephritis. Virtually all patients with C-ANCA had antibodies against proteinase 3, which corresponded with a clinical and/or histological diagnosis of Wegener’s granulomatosis (WG). P-ANCA were associated with antibodies against myeloperoxidase. Although more often associated with renal-limited disease, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 22 publications
3
17
0
Order By: Relevance
“…However, it was reported that sera from a minority of patients with cANCA recognized autoantigens other than PR3 (such as MPO) [17], which was supported by our previous study [15]. In the current study, sera with cANCA exclusively recognized PR3, and sera with pANCA exclusively recognized MPO.…”
Section: Discussionsupporting
confidence: 90%
“…However, it was reported that sera from a minority of patients with cANCA recognized autoantigens other than PR3 (such as MPO) [17], which was supported by our previous study [15]. In the current study, sera with cANCA exclusively recognized PR3, and sera with pANCA exclusively recognized MPO.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, apart from reflecting the functioning part of the kidney, normal glomeruli also are a relatively constant parameter, the combination of which may explain their strength as a predictive parameter. Also intraepithelial tubular infiltrates are predictive of GFR 12 , and their presence may well be related to the development of tubular atrophy, a widely known parameter of chronic renal failure in general and associated with worse renal outcome in ANCA-associated vasculitis (11,18).…”
Section: Discussionmentioning
confidence: 99%
“…Kidney biopsies were scored according to an activity index (AI) and chronicity index (CI, Table 2), which was adapted from the scoring system used in SLE [3,10]: semiquantitative scale (0-3; absent, mild, moderate, severe); necrosis, cellular, and fibrous crescents are multiplied by a factor of 2; the maximal AI is 24 and the maximal CI 18. Glomerular lesions were classified into four categories (Table 3).…”
Section: Histological Evaluationmentioning
confidence: 99%